Glutamate Systems in DSM-5 Anxiety Disorders: Their Role and a Review of Glutamate and GABA Psychopharmacology - Nasir, Madeeha; Trujillo, Daniel; Levine, Jessica; Dwyer, Jennifer B.; Rupp, Zachary W.; Bloch, Michael H. (Frontiers in Psychiatry, 2020)
Serotonin reuptake inhibitors and benzodiazepines are evidence-based pharmacological treatments for Anxiety Disorders targeting serotonin and GABAergic systems, respectively. Although clearly effective, these medications fail to improve anxiety symptoms in a significant proportion of patients. New insights into the glutamate system have directed attention towards drugs that modulate glutamate as potential alternative treatments for anxiety disorders. Here we summarize the current understanding of the potential role of glutamate neurotransmission in anxiety disorders and highlight specific glutamate receptors that are potential targets for novel anxiety disorder treatments. We also review clinical trials of medications targeting the glutamate system in DSM-5 anxiety disorders. Understanding the role of the glutamate system in the pathophysiology of anxiety disorder may aid in developing novel pharmacological agents that are effective in treating anxiety disorders.